Assessing the validity and intra-observer agreement of the MIDAM-LTC; an instrument measuring factors that influence personal dignity in long-term care facilities - Oosterveld-Vlug, Mariska G (BioMed Central, 2014)
BACKGROUND: Patients who are cared for in long-term care facilities are vulnerable to lose personal dignity. An instrument measuring factors that influence dignity can be used to better target dignity-conserving care to an individual patient, but no such instrument is yet available for the long-term care setting. The aim of this study was to create the Measurement Instrument for Dignity AMsterdam - for Long-Term Care facilities (MIDAM-LTC) and to assess its validity and intra-observer agreement. METHODS: Thirteen items specific for the LTC setting were added to the earlier developed, more general MIDAM. The MIDAM-LTC consisted of 39 symptoms or experiences for which presence as well as influence on dignity were asked, and a single item score for overall personal dignity. Questionnaires containing the MIDAM-LTC were administered face-to-face at two moments (with a 1-week interval) to 95 nursing home residents residing on general medical wards of six nursing homes in the Netherlands. Constructs related to dignity (WHO Well-Being Five Index, quality of life and physical health status) were also measured. Ten residents answered the questions while thinking aloud. Content validity, construct validity and intra-observer agreement were examined. RESULTS: Nine of the 39 items barely exerted influence on dignity. Eight of them could be omitted from the MIDAM-LTC, because the thinking aloud method revealed sensible explanations for their small influence on dignity. Residents reported that they missed no important items. Hypotheses to support construct validity, about the strength of correlations between on the one hand personal dignity and on the other hand well-being, quality of life or physical health status, were confirmed. On average, 83% of the scores given for each item’s influence on dignity were practically consistent over 1 week, and more than 80% of the residents gave consistent scores for the single item score for overall dignity. CONCLUSION: The MIDAM-LTC has good content validity, construct validity and intra-observer agreement. By omitting 8 items from the instrument, a good balance between comprehensiveness and feasibility is realised. The MIDAM-LTC allows researchers to examine the concept of dignity more closely in the LTC setting, and can assist caregivers in providing dignity-conserving care.